Factors predisposing to wrong blood in tube incidents: a year's experience in the North East of England. Issue 5 (29th June 2013) - Varey, A.; Tinegate, H.; Robertson, J.; Watson, D.; Iqbal, A.
Summary Introduction Wrong blood in tube (WBIT) describes a transfusion sample collected from one patient but labelled with the identification details of a different patient. These incidents have the potential to result in catastrophic harm to patients. In 2011, the Serious Hazards of Transfusion (SHOT) organisation received 469 reports of WBIT across the UK. What this study adds This was a prospective study of WBIT which collected information not only on the frequency of WBIT but also risk factors. Method All hospitals in the North East region of England submitted details of known WBITs during a 12‐month period starting from July 2011, including the time of day and location where samples were taken, the job title and competency of the sample taker, and how the WBIT was identified. Where possible, the sampler was interviewed to determine reasons for the WBIT. RESULTS There were 48 WBITs, giving a corrected incidence of 1 : 2717 repeat transfusion samples. Doctors were responsible for 24 of 45 WBITs where the identity of the sampler was known. The rate as a proportion of samples was highest in medicine and paediatric specialties. The commonest risk factor for WBIT was labelling away from the bedside (44%). Conclusions These findings support, and add to, the data collected by SHOT. If our figures are representative of the whole of the UK, then over 1160 WBITs will occur each year, justifying SHOT's concerns that WBITs are under reported. Interventions are needed to ensure labelling of transfusion samples is always carried out at the patient's side.